2015
DOI: 10.1186/s12879-015-1202-7
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistant tuberculosis: prevalence and risk factors in districts of metema and west armachiho, Northwest Ethiopia

Abstract: BackgroundMulti drug resistant tuberculosis (MDR-TB) is an emerging challenge for TB control programs globally. According to World health organization, 2012 report Ethiopia stands 15th out of the 27 high priority countries in the world and 3rd in Africa. Updated knowledge of the magnitude of MDR-TB is so substantial to allocate resources, and to address prevention and control measures. Therefore, the aim of this study was to assess the prevalence of MDR-TB and associated risk factors in West Armachiho and Mete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
81
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(115 citation statements)
references
References 15 publications
25
81
8
1
Order By: Relevance
“…In Ethiopia, 2.3% of new TB cases and 17.8% of previously treated TB cases were estimated to have MDR [3]. Studies in Ethiopia reported 4.7–18.3% prevalence of rifampicin-resistant M. tuberculosis [610]. Mutations in a ‘hotspot’ region of 81 base pairs (bp) of rpoB gene have been found in about 96% of rifampicin (RMP) resistant M. tuberculosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, 2.3% of new TB cases and 17.8% of previously treated TB cases were estimated to have MDR [3]. Studies in Ethiopia reported 4.7–18.3% prevalence of rifampicin-resistant M. tuberculosis [610]. Mutations in a ‘hotspot’ region of 81 base pairs (bp) of rpoB gene have been found in about 96% of rifampicin (RMP) resistant M. tuberculosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a study states that one important risk factor for acquiring MDR-TB is a history of previous TB treatment [13]. In contrast, for XDR-TB, the risk factors are family history of TB, socioeconomic status, co-morbidities, and previous intake of second-line injectable drugs [14]; while the risk factors for mortality from drug-resistant tuberculosis are previous TB episodes, diabetes history, education level, and HIV infection [15].…”
Section: Discussionmentioning
confidence: 99%
“…BCG vaccine is the only TB vaccine licensed for use in humans. BCG vaccine has variable levels of protection efficacy in humans against pulmonary TB in children and adults, ranging from 0-80% [68]. It is reported that the prevalence of MDR-TB in previously treated cases was 13.9% and in new cases only 2.3%, whereas the overall prevalence of MDR-TB was 5.7% in all cases [69].…”
Section: Treatmentmentioning
confidence: 99%